Strengthening Non-health Community-based Health Misinformation Management Structures: Learnings from a Capacity Building Fellowship in Niger State, Nigeria - Mr Abara Erim; Mr Sunday Oko; Ms Sonia Biose; Dr Kemisola Agbaoye; Ms Anwuli Nwankwo; Mrs Vivianne Ihekweazu (International Journal of Infectious Diseases)
Introduction: Vaccine-preventable disease outbreak response and vaccination rates are negatively impacted by rumors and false information. Erroneous information persists even after it has been corrected, negatively influencing health decisions and exacerbating health disparities while disproportionately impacting underprivileged communities. To overcome these challenges, community networks are essential - they can effectively advocate for public health initiatives while delivering accurate and culturally relevant information, which have a significant impact on community perception. By strengthening and leveraging these networks, we can be sure that accurate health information is distributed in a targeted and efficient manner to a variety of demographic groups, strengthening community resistance to false information. Thus, a fellowship program was piloted in Niger State, Nigeria to improve community networks’ capacities and reinforce their involvement in public health advocacy. Methods: The health misinformation management fellowship was designed using a bottom-up approach, starting with a needs assessment. It was conducted between August 2023 to January 2024. Following online applications, applicants went through a competitive selection process, and approximately 25 fellows representing 10 community network categories of religious, community, traditional, and media groups were selected. Fellows were initially trained in person over 3 days, with subsequent remote mentoring and support provided over subsequent months during which fellows conducted community listening and sensitization activities. The training approach was andragogic, with regular check-ins instituted for reporting and peer learning over the course of the fellowship. Results: The findings from the fellowship pre and post-test showed a significant 10% increase in knowledge and skill across the key knowledge areas of health misinformation, identification of health misinformation, and misinformation management. Fellows identified and addressed 15 rumours and misinformation within their communities and successfully engaged about 7,979 individuals, with 47% reached online and 53% offline; 33% of the offline participants were men, 60% were women, and 7% were children. Discussion: The Program demonstrated how community networks can be strengthened to identify and health misinformation. Comparable efforts, such as those by community health workers in South Asia and Sub-Saharan Africa, successfully improved health outcomes by addressing local misinformation and increasing immunization rates. While the participants of this fellowship were not healthcare workers, they proved to be effective as they leveraged their networks and the trust of their communities to reach a broader, more diverse audience, both online and offline. Conclusion: Non-health community actors are effective in the management of health misinformation when trained, as they are able to leverage the trust of their communities to reach a broader audience. Future research should focus on quantifying the long-term impacts of such interventions on vaccine uptake and public health outcomes, as well as exploring the scalability of this model to other regions and health challenges.